Selection of microalgae and cyanobacteria to produce polyhydroxyalkanoates (PHAs) - A case study in Vietnam - Thinh Thi Hai Pham; Thi Lan Anh Nguyen; Thuy Thi Duong; Oanh Thi Doan; Hien Thi Thu Tran; Lan Thi Thu Tran (Case Studies in Chemical and Environmental Engineering)
Microplastic pollution has been deemed a serious environmental concern for many developing countries, including Vietnam. Thus, bioplastics produced from sustainable materials by microorganisms have been sourced as an alternative to mitigating microplastic pollution. This study conducted the screening of 47 strains of microalgae and cyanobacteria sourced from various locations and environmental conditions in Vietnam for the production of polyhydroxyalkanoates (PHAs) as a source of bioplastics. The experimental results demonstrate that 15 out of the total 47 screened microalgae and cyanobacteria strains could produce PHAs, and they exhibited diverse PHAs production despite being grown under the same incubation conditions. Furthermore, amongst these 15 strains, Arthrospira platensis NLHT3, Microcystis aeruginosa DTB1, Arthrospira platensis NLNA2, and Arthrospira platensis NBQN1 exhibited the highest PHAs accumulation rates of 4.18 %, 3.46 %, 3.01 %, and 2.82 % of cell dry weight, respectively. The analysis of polymer granules accumulated inside the cell biomass by transmission electron microscopy (TEM) and Fourier-transform infrared spectroscopy (FTIR) confirms that the accumulated biopolymers were PHAs.